EARLY PLIOCENE LAGOMORPHS FROM TOLLO DE CHICLANA-1B (GUADIX BASIN, SPAIN): NEW PERSPECTIVES ON THE EVOLUTION AND THE PALEOBIOGEOGRAPHY OF LATE NEOGENE WESTERN EUROPEAN LAGOMORPHA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
The continental record of the Guadix Basin (southern Spain) documents a fundamental time-window for the evolution of leporids and prolagids. Here we provide the first attempt of a taxonomic revision of the lagomorphs of the Guadix Basin (Prolagus aff. michauxi, Trischizolagus aff. crusafonti, and Oryctolagus cf. laynensis), evidencing that, at least in southern Spain, the accepted taxonomic model should be reconsidered in light of a possible partly endemic evolutionary history of lagomorphs during the latest Miocene and Pliocene. Actually, our data highlight that there was a limited interchange between southern Iberian lagomorphs and those of the rest of western Europe at least since the late Turolian (MN13). Dispersals were instead active, in the early part of the MN13, from southern Iberia to northern Africa, a new territory where prolagids and leporids underwent local radiation and evolution.
Keywords: Prolagidae; Leporidae; Ruscinian; MN15b; taxonomy.